Implementation of Spatial Planning Law in Addressing Environmental Problems in Urban Areas - Rika Santina; Raja Agung Kesuma Arcaropeboka; Rendy Renaldy; Kamal Fahmi Kurnia; Arif Hidayatullah (International Journal of Law, Crime and Justice, 2024)
A city is one of the areas heavily populated by people. In Indonesia, there are a total of 98 cities. A city is a complex area because it has various zones such as central zones, industrial zones, and suburban zones. Additionally, a city should also have green open spaces. Green open spaces can help minimize global warming and the greenhouse effect in urban areas. Moreover, cities often grapple with waste issues. Urban residents should develop good mental attitudes and habits, such as not littering. Cooperation between the government, which builds proper and appropriate urban planning by providing green areas, and the public's awareness to maintain city cleanliness by disposing of waste properly, is necessary.